DETERMINAN TINGKAT KEMISKINANDI PROPINSI NUSA TENGGARA TIMUR (Periode 2011-2016) - Hilman Lutfi (Universitas Lambung Mangkurat, 2018)
The purpose of this study is to analyze the influence of Gross Regional Domestic Product,Literacy Rate and Life Expectancy Rate to Poverty Level. The data used in this study is secondary data obtained from the Central Bureau of Statistics of East Nusa Tenggara Province period 2011-2016. To find the relation between variables included in this research, the analysis technique used is time series data and the model used is Multiple Linear Regression Model. Result of research using fixed effect model found that Gross Regional Domestic Product have positive and significant effect to Poverty Level, while Literacy Rate and Life Expectancy Number have no significant influence to Poverty Level. The model used in this study deserves to explain the Poverty Level in East Nusa Tenggara Province for the Period 2011-2016.